THE ‘BRITISH-IMPERIAL’ MODEL OF ADMINISTRATION: ASSEMBLING THE SOUTH AFRICAN CONSTABULARY, 1900 – 1902 - Spencer, Scott C (Scientia Militaria - South African Journal of Military Studies, 2013)
With the end of the South African War believed to be in sight, British policymakers in South Africa created the South African Constabulary (SAC) in late 1900to provide law and order over the new Transvaal and Orange River colonies. By1900, policy makers no longer simply exported ‘English’ or ‘Irish’ models to thecolonies but sought guidance from existing institutions throughout the British Islesand Empire in a single ‘British-Imperial’ model of administration. Those policymakers and the new corps’ senior officers turned to the imperial policing networkfor ideas, methods, and particularly personnel to assemble the SAC, recruiting tenthousand officers and constables from across the British Isles and Empire. When itdisbanded eight years later, SAC veterans used the imperial policing network to takeup new positions in police forces throughout the British Isles and Empire. This‘British-Imperial’ model implemented a ‘best practices’ form of administration inwhich the men (and, very occasionally, women) who carried these practices enjoyedsuperior importance.